Revisiting the Congruence–Satisfaction Relationship: The Role of External Forces. (June 2019) - Fu, Mingchen; Zhang, Li-Fang; Li, Bing
The main objective of the present study was to explore the role of the forces in the context external to the setting of a specific vocational setting (i.e., an academic major in a university) in the congruence–satisfaction relationship. Four hundred and fifty-three Chinese university students responded to the Career Personality Styles Inventory, the revised Contextual Supports and Barriers Scale, and the Academic Major Satisfaction Scale. Results indicated that the congruence between individual vocational interests and their academic majors (for brevity, congruence) and two types of external forces (external barriers and support from social relations) were significant predictors of students' satisfaction with their academic majors. In comparison, the predictive power of external forces for students' satisfaction with their academic majors was far beyond that of congruence. Moreover, external barriers were a marginally significant moderator in the relationship between congruence and satisfaction. Implications and limitations of the findings are discussed.